Level of Understanding and Compliance Regarding the Rights and Obligations of BPJS Participants to Utilize Dental Health Services in the First Health Facilities - Erni Mardiati; Pudentiana Rr. R. E.; Irmanita Wiradona (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
The problem of oral health in the last five years increased by five years, by 25,9% to 57.6% of the total population of Indonesia. BPJS is a government health service facility that provides various dental health services. Community participation in the Health BPJS is critical to guarantee the right to obtain a healthy life. This study aims to determine the relationship between understanding and compliance with the obligations and rights of BPJS Health participants to the use of dental health services. The method in this study was observational with a cross-sectional design. The research sample was 117 people. Data were analyzed using a statistical application program consisting of a single univariate analysis, presented in the form of a frequency distribution and then described as well as a bivariate analysis to see the relationship of understanding and compliance regarding the obligations and rights of BPJS Health participants to the utilization of dental health services using the statistical test Spearman Rank. The results showed a significant relationship between the level of understanding and compliance regarding the obligations and rights of BPJS health participants, with p-value = 0,000 for the aspect of the level of understanding and p-value = 0.017 for the aspect of the level of compliance. It is recommended that the community further improve the level of understanding and compliance related to the obligations and rights of the health BPJS participants so that they can efficiently utilize the available health services.